Pricing and Promotion Analysis of Purchase Decisions at McDonald's - Azzahra Azzahra; Alza Syofyan Andri B; Zefriyenni Zefriyenni (Green Publisher Indonesia, 2025)
Indonesia's economic progress is experiencing rapid expansion, marked by growth across multiple sectors, particularly in the franchise industry. Amid increasingly fierce competition among similar businesses, companies are required to formulate and implement diverse strategies to anticipate and overcome competitive threats. This [A1] *[A2] study aims to analyze the influence of environmental factors, wage systems, coordination, and worker productivity on the performance of completion time for government building construction projects in Pangkalpinang City. Using the multiple linear regression method, this study found that these factors simultaneously contributed 85.4% to project completion. The analysis results show that the wage factor is the dominant factor with an influence contribution of 72.59%. Therefore, wage system management strategy is the main step in improving the efficiency of project completion time. The proposed solution to optimize the wage system includes the provision of skills-based wages, work duration-based compensation, achievement-based pay, work type differentiation, and the provision of incentives that encourage worker productivity. The results of this study are expected to provide insights for project managers in improving the effectiveness of completion time for government building construction projects.